The Video Campaign: Decision Making in The Quarter Life Crisis Phase - Ramadhani , Anggie Selvia; Putri, Eka Cahyani Aulia; Ardiningrum, Hapsari; Priyalita , Jenica; Annajah , Nabiilah; Wahyu Dwiastuty , Nabilla Putri; Hidayati , Nurul; Ugsang Acob, Joel Rey (Inovasi Lokal, 2023)
The development of media technology is very rapid and with advances in technology that are increasingly developing day by day, the use of social media which can be accessed from mobile phones, the dominance of social media which is widely used, such as Instagram, is a favorite among Indonesian people, especially young people, with the number of users accessing it. Instagram is around 79% with various campaigns or interesting content. The campaign regarding the Quarter Life Crisis that has been created will be uploaded to Instagram with the aim of finding out how informative and interesting the campaign uploaded to Instagram is for teenage Instagram users. A quarter-life crisis is a crisis condition experienced in their 20s. Someone who is in Quarter Life Crisis often experiences emotional problems, where he is always confused about the various available options. The method used to create the campaign was data collection method through random interviews with FIK students and using the publication method via Instagram. The results obtained were seen through Instagram insights with a total audience of 497 users, 106 users liked, 35 users commented and 21 users shared.